From stimulus to science - Quine, W. V. (Harvard University Press, 1995)
W. V. Quine is one of the most eminent philosophers alive today. Now in his mid-eighties he has produced a sharp, sprightly book that encapsulates the whole of his philosophical enterprise, including his thinking on all the key components of his epistemological stance--especially the value of logic and mathematics. New readers of Quine may have to go slowly, fathoming for themselves the richness that past readers already know lies between these elegant lines. For the faithful there is much to ponder.